DEVELOPING ENGLISH TEXTBOOK IN ELEMENTARY SCHOOL BASED BANYUWANGI LOCAL WISDOM IN BANYUWANGI REGENCY - nur hasibin; Arin Inayah (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2021)
This study aims to develop an English textbook based on Banyuwangi local wisdom. The design used is research and development (R&D) using Borg and Gall models, namely; 1) Preliminary study (define) and design (design); 2) Textbook development (Development); (3) the model testing phase, and 4) Dissemination of implementation (development, validation, and testing) of textbook development results. The collecting data is a qualitative data which is the result of interviews, questionnaires, and document analysis. There were 12 teachers as respondents in two sub-districts in Banyuwangi district, namely Kabat District and Banyuwangi District. Three experts in providing input on the research prototype. The results of this study indicate that the process of developing textbooks includes an introduction in the form of a map of the teacher's need for textbooks based on Banyuwangi local wisdom that most respondents want textbooks. The design stage includes a book draft, and the development stage is the final textbook result. Assessment of the quality of textbooks from the material, presentation, language, and graphics components. The material components got good ratings, good presentation, good language, and good graphics.